Computer-Based Examination System for the Licensure Examination of Agriculturist - Patayon, Urbano B.; Mandawe, Crisanto; Pagador, Chenee Rose; Teopis, Yvonne; Quiboyen, Jr., Elidio (JPAIR Multidisciplinary Research, 2017)
Computer-based examination plays an important role in the assessment process in the 21st century. The study aimed to develop a computer-based examination system intended for the Agriculture graduates who would like to review in preparation for the Licensure Examination for Agriculturist. The researchers utilized various web scripting languages and Content Management System (CMS) in developing different pages.  A descriptive survey was used to evaluate the capability of the system.  There were one hundred seventy-eight (178) students taking agriculture related courses requested as respondents of the study. The statistical treatment used in the study was weighted mean to determine the perception of the respondents utilizing the Likert five-point scale criteria. Based on the findings of the study, it showed that the developed computer-based examination system for the licensure examination for agriculturist is meaningfully accepted by the users, because of the high accessibility, functionality, and usability level of the system features. Based on the result of the data gathered when respondents are grouped according to sex, it is described that the system is highly accessible, very much functional, highly reliable and highly usable.  Therefore, this study should be adopted by the college, the review center of the school and other institutions across the country to help students review for their upcoming exams using this computer-based examination system.
Keywords: Information Technology; Computer-based examination; Descriptive survey; accessibility; functionality; usability; Philippines